Assessment of Dithiocarbamate Residues on Tomatoes Conventionally Grown in Uganda and the Effect of Simple Washing to Reduce Exposure Risk to Consumers. (2nd June 2017) - Atuhaire, Aggrey; Kaye, Emmanuel; Mutambuze, Innocent Louis; Matthews, Graham; Friedrich, Theodor; Jørs, Erik
Pesticide misuse by farmers poses health risks to consumers. This study assessed the level of dithiocarbamate residues in tomatoes acquired from 20 farmers and 25 market vendors in Wakiso District, how simple washing affects these residues, and the potential chronic health risk for Ugandans eating such tomatoes. Results revealed that mancozeb was the only reported dithiocarbamate, and 47.4% and 14% of farm and market samples, respectively, had dithiocarbamate residues exceeding the Codex alimentarius maximum residue limit of 2 mgCS2 /kg. Mixing concentration had a positive significant effect on dithiocarbamate residue levels ( P = 0.004). Washing reduced dithiocarbamate residues by a factor of 0.3. Dietary risk assessment revealed no chronic health risk to both children and general population when a national daily per capita consumption of 1.0 g is considered. This study recommends comprehensive research into Uganda's food production and consumption patterns and establishment of a national pesticide residue surveillance program.